Predictability of the quasi-biennial oscillation driven by land-sea breezes. - Wan, Fang (2014)
This dissertation studies the predictability of the quasi-biennial oscillation (QBO) driven by land-sea breezes. Particularly, the proposed subject is approached through an idealized numerical model of the QBO driven by land-sea breezes, and analysis of separation-growth dynamics of the idealized numerical model. Implicit to the definition of separation growth is the fundamental concept of a metric, i.e. the distance between two states in the phase space. We suggest that some energy metrics are based on linearization and hence it may not be appropriate to apply these metrics when two states are far apart, such as encountered in the real atmosphere. A new approach to define the energy metric is proposed and it is used to study the separation-growth dynamics in the idealized model.